Heavy metal pollution exposure affects egg coloration but not male provisioning effort in the pied flycatcher Ficedula hypoleuca - Mari, Lisandrina; Sulc, Michal; Szala, Klaudia; Troscianko, Jolyon; Eeva, Tapio; Ruuskanen, Suvi (John Wiley & Sons, 2025)
Heavy metal pollution is known to negatively affect numerous traits in birds, including foraging, metabolism, immunity, and reproductive success. In this study, our primary aim was to assess the impact of metal pollution exposure on the visual appearance of the pied flycatcher Ficedula hypoleuca eggs. Specifically, we focused on blue-green biliverdin-based coloration, a trait expected to function as a signal of female quality to males. In line with the sexually selected egg coloration (SSEC) hypothesis, which posits that males respond to more intensely colored eggs by increasing their provisioning effort, our second objective was to investigate whether metal pollution exposure affects this specific signaling mechanism and subsequent male behavior. Our results showed that although coloration did not correlate with female quality or male provisioning effort, egg blue-green coloration decreased in polluted areas compared to non-polluted control areas. Our analysis of reflectance data revealed that this difference was due to an increased ultraviolet reflectance of eggs from polluted areas, likely caused by changes in eggshell microstructure (e.g. porosity). We therefore propose that metal pollution exposure may compromise crucial color signals of bird eggs. Avian visual modeling indicated that eggs laid by different flycatcher females are generally very similar, making discrimination by males challenging and perhaps impossible especially in dark cavities. Overall, our results suggest that the SSEC hypothesis may lack adaptive relevance for the pied flycatcher in northern Europe, even in environments influenced by anthropogenic activities.